A Role of Ergonomics in Advanced Manufacturing Systems: A Harmonious Blend of Human and Machine - Darshan H. Bhalodia; Rishabh D. Makwana; Parth M. Lakum; Heena M. Patel; Rohit R. Raval (International Journal of Manufacturing and Production Engineering, 2025)
The integration of human and machine elements in advanced manufacturing systems (AMS) necessitates a careful consideration of ergonomic principles to ensure the well-being and performance of the workforce. This paper explores the critical role of ergonomics in AMS, focusing on physical, cognitive, and organizational aspects. By optimizing the interaction between humans and technology, ergonomics aims to reduce musculoskeletal disorders, improve worker satisfaction, and enhance overall system efficiency. The paper delves into specific ergonomic considerations in AMS, such as workstation design, tool and equipment selection, work organization, and training. Furthermore, it discusses the potential benefits of incorporating ergonomic principles into AMS, including reduced injuries, improved quality, and increased worker morale. By striking a balance between technological advancements and human well-being, ergonomic design can contribute to the sustainable development of advanced manufacturing systems. The research highlights how ergonomics can improve the interface between operators and machines, ensuring that both human skills and machine capabilities are maximized for productivity and safety. Through an exploration of practical case studies, the paper illustrates the tangible benefits of ergonomics in advanced manufacturing settings, including reduced error rates, improved system adaptability, and increased operational efficiency. By fostering an ergonomic approach, advanced manufacturing systems not only improve worker well-being but also contribute to the sustainability and long-term success of manufacturing operations in the face of technological transformation. This work underscores the need for interdisciplinary collaboration between engineers, designers, and ergonomics experts to create manufacturing environments that are both technologically advanced and human-centered.
Keywords: Human-machine interface design; Industry 4.0; advanced manufacturing system; ergonomics; workstation